Pseudonimitas dan Ineransi Perjanjian Baru: Tinjauan Historis terhadap Literatur Yahudi, Greco-Roman, dan Kristen Awal - Sanjaya, Abraham (Sekolah Tinggi Teologi Injili Indonesia Palu, 2026)
The issue of pseudonymity is frequently raised regarding several books in the New Testament, which, if proven true, would have serious implications for the concept of biblical inerrancy. This study aims to evaluate the function of pseudonymity in Jewish literature, its understanding in the Greco-Roman world, the early church’s assessment of pseudonymous writings, and their implications for inerrancy. The method used is library research with a descriptive qualitative approach based on literature study, combining historical and theological analysis. The results show that pseudonymity emerged with various motives across all three cultural contexts, yet its acceptance was not universal. The early church consistently rejected pseudonymous writings and ostracized their authors, in contrast to the Greco-Roman context, which in certain situations accepted them. In conclusion, integrating historical findings with the doctrine of inerrancy yields three implications: apostolicity as the normative foundation of inerrancy, the incompatibility of pseudonymity with the nature of God’s truth, and the lack of sufficient historical basis to consider the New Testament canon as containing pseudonymous documents.